PENERIMAAN DAN PENOLAKAN ISLAM NUSANTARA DI KALANGAN ULAMA KOTA PALEMBANG - Muhamad Harun (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2020)
This article takes a focus on the acceptance and rejection of Nusantara Islam among the Ulama of Palembang City. The background of this article is the socio-religious phenomenon seen in the Ulama of Palembang City showing different variants and expressions in addressing the term of Islam in Nusantara. A qualitative descriptive approach is used to answer the two questions raised in this article. First, what is the motive for the rejection of Nusantara Islam among the ulama of Palembang City, and second, what is the motive for the acceptance of Nusantara Islam among the ulama of Palembang City? The author found that knowledge, experience, and interests were motives for the rejection of Nusantara Islam among the old Palembang. Meanwhile, the motives for acceptance of Nusantara Islam among the Palembang Ulama include incentives, group solidarity, learning, and compulsion.